The Horizons of Parental Co-Responsibility in Ibero-America - Molina-Ricaurte, Carlos Jesús (PRAWO i WIĘŹ, 2026)
This study examines the implementation of paternity and parental leave policies across Ibero-America, drawing attention to the similarities and differences between countries in the region. An exploratory review was conducted in Scopus. The results were filtered by time. Matches were then found based on abstracts and keywords. Official repositories were subsequently consulted to validate the results. Finally, the search was expanded to Google Scholar, which provided additional information and enabled the selection of three relevant cases (Chile, Colombia and Spain). This limited the analysis to the Ibero-American sphere. The results revealed significant variations in leave duration and usage, suggesting which countries are more likely to foster greater paternal involvement and reduce gender inequality in the workplace. The study discusses how differences in legislation and policies impact fathers’ involvement in childcare and its relation to workplace gender equality. The study highlights the need to strengthen family protection frameworks and parental co-responsibility models in Ibero-America, in order to support a more equitable distribution of childcare responsibilities within families, and to promote gender equality in the workplace and in wider society. In short, the study provides a critical analysis of parental models across Ibero-America, with the aim of informing changes in family dynamics and labour practices throughout the region.